No Search Result Left Behind: Branching Behavior with Browser Tabs - Huang, Jeff; Lin, Thomas; White, Ryen W. (Proceedings of WSDM, 2012)
Today's Web browsers allow users to open links in new windows or tabs. This action, which we call `branching', is sometimes performed on search results when the user plans to eventually visit multiple results. We detect branching behavior on a large commercial search engine with a client-side script on the results page. Two- fifths of all users spawned new tabs on search results in the timeframe of our study; branching usage varied with different query types and vertical. Both branching and backtracking are viable methods for visiting multiple search results. To understand user search strategies, we treat multiple result clicks following a query as ordered events to understand user search strategies. Users branching in a query are more likely to click search results from top to bottom, while users who backtrack are less likely to do so; this is especially true for queries involving more than two clicks. These findings inform an experiment in which we take a popular click model and modify it to account for the diff ering user behavior when branching. By understanding that users continue examining search results before viewing a branched result, we can improve the click model for branching queries.